A locally compact quantum group of triangular matrices - Fima, P.; Vainerman, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We construct a one parameter deformation of the group of 2 × 2 upper triangular matrices with determinant 1 using the twisting construction. An interesting feature of this new example of a locally compact quantum group is that the Haar measure is deformed in a non-trivial way. Also, we give a complete description of the dual C*-algebra and the dual comultiplication.